The Effect of Carrot Juice Consumption on Blood Glucose Levels Among Individuals with Diabetes Mellitus in the Piyeung Health Center Area, Montasik Subdistrict, Aceh Besar Regency - Ulkhairi, Anisa; Fitri, Yulia (JAND: Journal of Applied Nutrition and Dietetic, 2025)
Diabetes mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels resulting from impaired insulin production or utilization. In addition to pharmacological therapy, blood glucose control can be supported through the use of herbal interventions such as carrot juice. Carrots (Daucus carota L.) are low calorie, high fiber vegetables rich in antioxidants, including vitamin C, β-carotene, lycopene, and flavonoids which may protect pancreatic β-cells and help reduce blood glucose levels. This study aimed to examine the effect of carrot juice consumption on blood glucose levels among individuals with diabetes mellitus. A quasi-experimental design with a pre-test–post-test control group was employed at the Piyeung Health Center, Montasik Subdistrict, Aceh Besar Regency. A total of 32 participants were selected using purposive sampling and divided into two groups: the treatment group, which received carrot juice daily for seven days, and the control group, which received mineral water for the same duration. Blood glucose levels were measured using an Easy Touch device. Data were analyzed using paired and independent t-tests in SPSS, and the results were presented in tabular and textual form. The mean blood glucose level before carrot juice administration was 221.88 mg/dL, which decreased to 199.88 mg/dL after the intervention, indicating a reduction of 22.0 mg/dL. The findings demonstrate that carrot juice consumption significantly reduces blood glucose levels among individuals with diabetes mellitus in the Piyeung Health Center area (p < 0.05).